Status of Women In Polygamous Marriages and Need for Legal Protection: Book Review - Devi Sri Rahayu (Journal of Islamic Studies and Education, 2025)
The Status of Women in Polygamous Marriages and the Need for Legal Protection The need for Legal protection by Noorjehan & Soman (2022) for women in polygamous marriages is a book with the genre of social knowledge or activism and social law. the book explains that Muslim women are deprived of legal protection in family law matters in India. The need to demand comprehensive reforms in family law in accordance with the Quranic injunctions on gender justice and the constitutional principles of fairness, equality and non-discrimination.